Comparative study of graphene and carbon nanotube based field effect transistor for biosensing. - Hoo, Tun Kai. (2010)
Nano-sized carbons such as graphene and carbon nanotubes have been used as highly sensitive semiconducting materials in field effect transistor (FET) based biosensors. Extensive studies have been made for each carbon material for biosensing but only a few ventures into a comparison study. For this project, a top-gating FET design was utilized to measure the bio-analytes’ modulation of the graphene and carbon nanotubes’ conductance. The device was fabricated using a micro-molding in capillary technique (MIMIC) to form micro-patterned graphene and carbon nanotubes devices for biosensing. The dimension of the micro-pattern improves compatibility with cell biosensing and it introduces an efficient electron transport pathway for better device conductance. The target analytes for this project were dopamine molecules and mercury (II) nitrate ions, which were added in increasing concentrations into a phosphate buffered saline (PBS) buffer solution filled FET device. Results from dopamine testing have shown that FET devices using carbon nanotubes possess superior sensitivity and detection range compared to graphene FET devices due to several explanations proposed. However, the detection results for charged ions (from mercury (II) nitrate) by both devices were debatable due to a lack of understanding of adsorption mechanism. Further studies can be done to remedy the above issue and specific binding of the analytes to functionalized devices can be carried out for a more thorough comparative study.